A Micelle Electrolyte Enabled by Fluorinated Ether Additives for Polysulfide Suppression and Li Metal Stabilization in Li-S Battery - Zhao, Yangzhi; Fang, Chen; Zhang, Guangzhao; Hubble, Dion; Nallapaneni, Asritha; Zhu, Chenhui; Zhao, Zhuowen; Liu, Zhimeng; Lau, Jonathan; Fu, Yanbao; Liu, Gao (Frontiers in Chemistry, 2020)
The Li-S battery is a promising next-generation technology due to its high theoretical energy density (2600Wh kg-1 ) and low active material cost. However, poor cycling stability and coulombic efficiency caused by polysulfide dissolution have proven to be major obstacles for a practical Li-S battery implementation. In this work, we develop a novel strategy to suppress polysulfide dissolution using hydrofluoroethers (HFEs) with bi-functional, surfactant-like amphiphlic design: a polar lithiophilic “head” section attached to a fluorinated lithiophobic “tail.” A unique solvation mechanism is proposed for these solvents whereby dissociated lithium ions are readily coordinated with lithiophilic “head” to induce self-assembly into micelle-like complex structures. Complex formation is verified experimentally by changing the additive structure and concentration, verified by small angle X-ray scattering (SAXS). These HFE-based electrolytes are found to be able to prevent polysulfide dissolution and to have excellent chemical compatibility with lithium metal: Li||Cu stripping/plating tests reveal high coulombic efficiency (>99.5%), modest polarization, and smooth surface morphology of the deposited lithium. Li-S cells are demonstrated with 1410 mAh g-1 initial capacity and 71.9% retention over 100 cycles at >99.9% efficiency—evidence that the micelle structure of the amphiphilic additives in HFEs can prohibit polysulfide dissolution while enabling facile Li+ transport and anode passivation.